Helicobacter pyloriInfection in Different Age Groups of Patients with Gastric Diseases. - Kareem Thamir Al-Kaaby; Israa Saeed Abbas (Kufa Journal for Nursing Sciences)
Background: Helicobacter pylori (H. pylori) is a harmful, medically important, pathogenic bacteria that colonizes stomach of different age groups. Therefore, it is important to conduct research on this particularly wide-spread bacteria.